OVERWEIGHT, A CULPRIT AFFECTING BACK ENDURANCE: A CROSS SECTIONAL STUDY - B. Shah, Nikhil; Kadu, Swati; B. Anap, Deepak; Mamania, Jinal A (International Journal of Clinical and Biomedical Research, 2017)
Background: Studies reveal that reduced muscle endurance has a major impact, leading to decrease in quality of life. Hence early diagnosis and prognosis is essential for leading healthy life. Lack of muscle endurance has shown to be related to decreased proprioceptive awareness and decreased productivity in the workplace and daily activity. Hence, the purpose of this study was to evaluate isometric endurance time of healthy normal population for trunk extensors and flexors. Method: In this cross-sectional study, 100 participants were randomly recruited by convenient sampling and trunk muscle endurance was assessed using trunk flexor endurance test and Sorensen's test. Results: The results of the study revealed-mean back endurance for extensor muscles was 47.66secs and 52.82secs for males and females respectively. Similarly, for trunk endurance for trunk flexors was 52.82 secs and 112.86 secs for males and females respectively. Conclusion: The study concluded that trunk muscle endurance for females was more as compared to males and also, with increase in BMI there is decrease in trunk muscle endurance. KEYWORDS: Trunk endurance; BMI; Sorensen's test; Trunk.